Innovating for diversity: a shariah-compliant model of human milk traceability in hospital settings - Ghazali, Mazlinah; Hashim, Khairusy Syakirin Has-Yun; Jamaludin, Mohammad Aizat; Muda, Siti Mariam; Ismail, Hamizah (Med & Health, 2025)
Introduction: Human milk banking (HMB) is globally recognised for its role in improving neonatal survival. However, in Muslim communities, it requires careful attention to milk kinship (raḍāʿah) and Shariah compliance. A traceability system to protect lineage (nasl) while ensuring Shariah compliant processes in donor human milk (DHM) is essential. This review examines how Shariah compliant HMB models address operational diversity, particularly in relation to traceability and documentation of kinship in hospitals. Methods: A narrative review was conducted of published studies, conceptual papers, and reports from 2015 to 2025. Sources were synthesised to capture current approaches to donor intake, milk labelling, storage and tracking, consent procedures, and kinship safeguards. The review emphasised diversity in healthcare practice, ethical integration, and shariah-compliant governance. Results: The review identified three main themes. First, ethical and religious safeguards are central, as documentation of milk feeding in HMB requires informed consent to ensure Shariah compliance. Second, different operational models were observed, with variations in milk collection, distribution, and digital record-keeping practices. Third, cultural and societal acceptance emerged as a critical factor, where public trust and effective governance strongly influenced the success and sustainability of HMB. Taken together, these findings highlight traceability as the essential link that binds medical safety, accountability, and religious integrity. Conclusion: Shariah-compliant HMB requires more than clinical adaptation; it calls for structured integration of Islamic ethics, kinship protection, and technological innovation. The novelty of this work lies in positioning traceability as a key pillar of diversity in Shariah-compliant healthcare for premature infants. This model connects ethical, clinical, and governance dimensions, offering guidance for policymakers, healthcare professionals, and Islamic institutions across ASEAN who seek to advance shariah-compliant healthcare.